Smooth muscle Ca2+ sensitization causes hypercontractility of middle cerebral arteries in mice bearing the familial hemiplegic migraine type 2 associated mutation. Issue 8 (August 2019) - Staehr, Christian; Hangaard, Lise; Bouzinova, Elena V; Kim, Sukhan; Rajanathan, Rajkumar; Boegh Jessen, Peter; Luque, Nathan; Xie, Zijian; Lykke-Hartmann, Karin; Sandow, Shaun L; Aalkjaer, Christian; Matchkov, Vladimir V
Familial hemiplegic migraine type 2 (FHM2) is associated with inherited point-mutations in the Na, K-ATPase α2 isoform, including G301R mutation. We hypothesized that this mutation affects specific aspects of vascular function, and thus compared cerebral and systemic arteries from heterozygote mice bearing the G301R mutation (Atp1a2 +/−G301R ) with wild type (WT). Middle cerebral (MCA) and mesenteric small artery (MSA) function was compared in an isometric myograph. Cerebral blood flow was assessed with Laser speckle analysis. Intracellular Ca 2+ and membrane potential were measured simultaneously. Protein expression was semi-quantified by immunohistochemistry. Protein phosphorylation was analysed by Western blot. MSA from Atp1a2 +/−G301R and WT showed similar contractile responses. The Atp1a2 +/−G301R MCA constricted stronger to U46619, endothelin and potassium compared to WT. This was associated with an increased depolarization, although the Ca 2+ change was smaller than in WT. The enhanced constriction of Atp1a2 +/−G301R MCA was associated with increased cSrc activation, stronger sensitization to [Ca 2+ ]i and increased MYPT1 phosphorylation. These differences were abolished by cSrc inhibition. Atp1a2 +/−G301R mice had reduced resting blood flow through MCA in comparison with WT mice . FHM2-associated mutation leads to elevated contractility of MCA due to sensitization of the contractile machinery to Ca 2+, which is mediated via Na, K-ATPase/Src-kinase/MYPT1 signalling.